Formulating Employability Skills for Graduates of Public Health Study Program - Nurul Qomariyah; Titi Savitri; Tridjoko Hadianto; Mora Claramita (Institute of Advanced Engineering and Science, 2016)
Employability skills as non technical skills are important for effective and successful individual participation in the workplace. The main aims of the research were to identify important employability skills needed by graduates of Public Health Study Program Universitas Ahmad Dahlan (PHSP UAD) and to assess the achievement of the employability skills development that has been carried out by PHSP UAD. This study used a mixed method research with convergent design. Quantitative research was conducted with survey to graduates. Qualitative research was conducted with structured interviews to employers. Both data were analyzed separately and interpreted concurrently. Graduates and employers of PHSP UAD in broad outline were in line on the important employability skills needed in the workplace and the assessment of the achievement. Several employability skills consistently were considered important. The achievement of employability skills that were related to public health knowledge and its application was high, meanwhile the achievement of several important employability skills which are needed in the work place in the 21st were low. Employability skills needed for graduates of PHSP UAD were formulated. Curriculum revision is recommended to integrate employability skills into core activities to promote the development of employability skills of PHSP UAD graduates.